Pengaruh Penggunaan Media Sosial dan Electronic Word Of Mouth Terhadap Keputusan Pembelian di Mediasi Oleh Ke-percayaan pada Mahasiswa di Kota Surakarta - Fadiyah Luthfiyani; Aniek Hindrayani (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study examines the effect of social media and electronic word of mouth on purchasing decisions through trust among students in Surakarta. The problem in this study is how social media and e-WOM directly and indirectly influence purchasing decisions, with trust as a mediating variable. The objectives of this study include the direct influence of social media and e-WOM on purchasing decisions and trust, as well as the influence of trust on purchasing decisions, including the mediating role of trust in the relationship between social media and e-WOM and purchasing decisions. The research method used is descriptive quantitative with primary data collection through closed questionnaire. The sample consisted of 388 students selected using purposive sampling. Data analysis was performed using Structural Equation Modeling (SEM) with SmartPLS software. The results showed that the use of social media and e-WOM had a positive and significant effect on purchasing decisions and trust. In addition, trust was found to have a positive and significant effect on purchasing decisions. The findings also indicate that trust mediates the relationship between social media and e-WOM usage and purchasing decisions in a significant and positive manner. Thus, this study concludes that both social media and e-WOM can directly and through trust encourage purchasing decisions among students. The implications of these findings are relevant for digital marketing strategies that utilize social media and e-WOM to increase consumer loyalty and purchasing decisions.